The Self-Organization of a Spoken Word - Holden, John G.; Rajaraman, Srinivasan (Frontiers in Psychology, 2012)
Pronunciation time probability density and hazard functions from large speeded word naming data sets were assessed for empirical patterns consistent with multiplicative and reciprocal feedback dynamics—interaction dominant dynamics. Lognormal and inverse power-law distributions are associated with multiplicative and interdependent dynamics in many natural systems. Mixtures of lognormal and inverse power-law distributions offered better descriptions of the participant’s distributions than the ex-Gaussian or ex- Wald—alternatives corresponding to additive, superposed, component processes. The evidence for interaction dominant dynamics suggests fundamental links between the observed coordinative synergies that support speech production and the shapes of pronunciation time distributions.